Protecting the worker-citizen abroad: duty of care beyond the state?. Issue 4 (7th August 2016) - Okano-Heijmans, Maaike; Caesar-Gordon, Matthew
Abstract : Ministries of foreign affairs (MFAs) are long acquainted with the challenge of ensuring the security of their nationals overseas. Likewise, private businesses assigning staff on foreign placements owe a "duty of care" to these worker-citizens. The growing prevalence of worker-citizens in high-risk areas showcases the myriad complexities involved in this dynamic, whereby governmental and private sector responsibilities towards worker-citizens frequently overlap and stand to gain from enhanced collaboration. Differences in approaches abound, such as small enterprises facing very different challenges to multinational corporations, and vice versa. A geographical split has likewise emerged, with European companies pursing greater privatization as a means to mitigate threats to worker-citizens. Their East Asian counterparts however have adopted strategies of securitization, a position denoting greater government proximity to worker-citizens. The impact of the duty of care therefore extends beyond worker-citizens, and likewise beyond MFA and private sector collaboration. Rather it impacts wider foreign policy considerations, challenging long-held stances such as non-intervention and providing governments with opportunities to deepen overseas involvement.